Effects of Biochar on Growth, Response to Water Stress, and Post-Stress Recovery in Underutilized Vegetable Hibiscus sabdariffa from Malawi - Dickson Mgangathweni Mazibuko; Sarvesh Maskey; Kiseki Kurashina; Hiromu Okazawa; Hiroyuki Oshima; Taku Kato; Hidehiko Kikuno (Crops)
Globally, Hibiscus sabdariffa L. (Malvaceae), commonly known as roselle or hibiscus, is a multipurpose vegetable crop. In Malawi, where it is referred to as ‘Chidede’ (Chichewa), it is recognized as an underutilized traditional plant with significant potential. Traditional vegetable production in Malawi is being promoted to enhance nutritional food security and climate change mitigation. Recently, biochar has become increasingly used to improve agricultural productivity through climate-smart technologies. To date, the influence of rice husk biochar (RHB) on H. sabdariffa remains underexplored. This study aims to evaluate the effects of RHB on the vegetative growth, response to water stress, and post-stress recovery of H. sabdariffa using a greenhouse pot experiment. Our findings indicate that biochar-amended soil enhanced plant height, stem thickness, and total leaf area by 16.5%, 12.0%, and 12.9%, respectively. Water stress significantly reduced all assessed growth parameters (p < 0.05) except total leaf area and average leaf area per plant. Under water stress conditions, biochar-treated plants were significantly taller (p < 0.05) and had a higher specific leaf area (p < 0.05), demonstrating a positive effect. A post-stress recovery analysis revealed that H. sabdariffa fully recovered in height and biomass, while partial recovery was observed for root collar diameter and compensatory recovery for total leaf area and average leaf area. Biochar-treated plants exhibited superior post-stress recovery compared to those grown in unamended soil. Overall, plants grown with biochar were taller and had a larger root collar diameter, higher stem and leaf fresh biomass, and greater total leaf area. These findings underscore biochar’s potential as a sustainable soil amendment for enhancing growth and resilience in underutilized crops. Further studies should explore field experiments to access environmental heterogeneity and examine the diverse factors influencing biochar efficiency.